Pengetahuan, Sikap dan Ketrampilan Wanita Tani dalam Pengelolaan Sampah di Wilayah Pesisir Kelurahan Srengsem - Safitri, Yuli; Rangga, Kordiyana K; Listiana, Indah (Suluh Pembangunan : Journal of Extension and Development, 2021)
The purpose of this study was to determine the level of knowledge of coastal communities in waste management, to determine the level of attitudes of coastal communities in waste management and to determine the level of skills of coastal communities in waste management. This research was conducted in Srengsem Village, Panjang District, Bandar Lampung. Data collection in this study was conducted in October-November 2020. Respondents were 40 female farmers who participated in KWT Kenanga. This study used a survey method with a quantitative descriptive approach. The results from this research are the level of knowledge and attitudes of coastal communities in waste management was classified as high but not yet supported by concrete actions or skills, meaning that the community had made waste reduction and handling such as simply processing waste into planting media and accommodating waste in one container so that it would not be scattered. however, they have not fully implemented the Reduce, Reuse and Recycle management Keywords: Knowledge, attitudes, skills, waste management